Reflection of Religious Practices of Indonesian Society in Joko Pinurbo’s Poetry - Edwar, Valentina Edellwiz; Fakhrunnisa, Ritma; Safitri, Fajar Diana; Nabila, Atika Silma (Gurindam: Jurnal Bahasa dan Sastra, 2025)
This study aims to analyze the empty space in Joko Pinurbo’s poetries with Iser's reception theory, especially the concept of unbesthimmheit (empty space), which can be filled by interpreting the text based on the reader's repertoire. The research method is descriptive qualitative. The analysis is carried out by identifying the repertoire, empty space, filling the empty space, actualizing meaning, and interpreting the aesthetic effect. The results of the study are: 1) visual form, titimangsa, and diction are clues that refer to the repertoire, namely religious practices in Indonesia in 2015-2016, 2) empty space in the form of metaphorical ambiguity and the absence of explanation of causal relations in the text, 3) empty space is filled with SARA conflicts and identity polarization, especially the case of Ahok and Meiliana as defendants in blasphemy, 4) aesthetic interpretation in the form of reflection on religious practices that are trapped in rituals so that they are vulnerable to intolerance, the solution is the actualization of love for others.